Peningkatan Hasil Belajar Ipas Melalui Model Game Based Learning Berbantu Media Puzzle Pada Peserta Didik Kelas V - Mutiara Syafa Maharani Putri; Subhanadri; Dhini Mufti (CV. DIGITIAL EDUKASI NUSANTARA, 2026)
Science and social studies (IPAS) learning in class V of SD Negeri 95/II Muara Bungo was still dominated by verbal delivery of material and one-way interaction, resulting in low student engagement and instructional media that had not been optimally utilized. This condition contributed to low learning outcomes in the topic of environmental damage, with only a small proportion of students reaching the Learning Objective Achievement Criteria (KKTP). This study aimed to describe the improvement of the learning process and learning outcomes of fifth-grade students through the application of the Game Based Learning model assisted by puzzle media. The study used a Classroom Action Research (CAR) design following the Kemmis and McTaggart model, conducted in two cycles, each consisting of planning, action, observation, and reflection. The subjects were 22 fifth-grade students. Data were collected through observation, tests, and documentation, then analyzed descriptively using percentages, mean scores, and classical mastery levels. The results showed that the students’ learning process improved from the poor category in cycle I to entirely good and very good categories in cycle II. Learning outcomes also improved from cycle I to cycle II, with classical mastery exceeding the established success indicator. It can be concluded that the application of the Game Based Learning model assisted by puzzle media is effective in improving the learning process and outcomes of IPAS, and can therefore be adopted as an innovative learning strategy alternative for elementary school teachers. Keywords: Game Based Learning; Puzzle Media; Learning Outcomes; Classroom Action Research